1983
DOI: 10.1111/j.1528-1157.1983.tb04633.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Blind Crossover Trial of Progabide Versus Placebo in Severe Epilepsies

Abstract: In this double-blind, two-period, crossover trial with randomized treatment assignment, progabide (+/- 30 mg/kg/day) and placebo were compared as add-on to standard therapy in 20 "therapy-resistant" epileptic patients (11 males, nine females; age range, 7-47 years). The duration of each treatment period was 6 weeks. Crossover was performed gradually over 3-4 days. Twenty-four patients entered the study: three dropped out for reasons unrelated to progabide effects; one dropped out during the placebo period beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 10 publications
3
19
0
Order By: Relevance
“…Combined data from the studies cited (22)(23)(24)(25)(26). From the published data, one measurement per patient was taken at random.…”
Section: Fig 1 Amentioning
confidence: 99%
See 1 more Smart Citation
“…Combined data from the studies cited (22)(23)(24)(25)(26). From the published data, one measurement per patient was taken at random.…”
Section: Fig 1 Amentioning
confidence: 99%
“…In five articles, the number and dose of all AEDs (but not serum levels) and AE were reported per patient (22)(23)(24)(25)(26). The total AED load in relation to the number of AE in individual patients is shown in Fig.…”
Section: A E and Doseherum Levels Reported Per Individual Patientmentioning
confidence: 99%
“…Some of the European clinical trials have shown it to be effective (Van der Linden et al, 1981;Loiseau et al, 1983;Weber et a]., 1983;Martinez-Lage et al, 1984), while results of other studies have been less favorable (Dam et al, 1983;Schmidt, 1984). PGB was the first drug to be tested by the Epilepsy Branch of the National Institutes of Health (NIH) under the Antiepileptic Drug Development Program (Leppik et al, 1985).…”
mentioning
confidence: 96%
“…The drug was evaluated in two controlled studies of patients with severe epilepsy, both suggesting a positive effect (Loiseau et al, 1981;van der Linden et a]., 1981).…”
mentioning
confidence: 99%